Otimização de rede GPON utilizando colônia de formigas - Pinto, Francisco Jonas Silva (2022)
The following term paper presents the implementation process of a metaheuristic algorithm, the ant colony optimization algorithm (ACO), for the creation of a gigabit-capable passive optical network (GPON) in Sobral downtown by using fiber to the home (FTTH) architecture with mixed topology. It is worth pointing out that planning a GPON network is an arduous and complex task that involves the geographical determination of the positioning of different types of equipment, fiber optic cables, and several other relevant parameters for the proper functioning of the network. Therefore, the ACO minimizes the implementation costs. The use of two techniques served to compare the proposed ACO solution. The random assignment generates random solutions and the so-called manual technique, in which the designer elaborates the solution. Finally, the ACO reduces the network final cost concerning the other two exposed solutions besides maintaining technical viability.